Preparation method and application of plastic composite hard sheet

By adding ECG@PVDC composite emulsion and NCC@PU adhesives to PVC/PU/PVDC composite hard films, and using surface electrostatic and hot air drying technology to prepare PVC/ NCC@PU/ECG@PVDC composite hardcore solves the problem of poor aging resistance of the existing composite hard film.

CN117487224BActive Publication Date: 2025-01-28ZHEJIANG UNIV OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311352580.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-01-28
Estimated Expiration
2043-10-19

AI Technical Summary

Technical Problem

The existing PVC/PU/PVDC composite hard sheets have problems such as poor aging resistance and are susceptible to heat and ultraviolet radiation, resulting in yellowing of the PVDC layer.

Method used

By dissolving ECG powder in PVDC lotion to prepare ECG@PVDC composite emulsion, and add nano cellulose NCC to the water -based polyurethane adhesive to prepare NCC@PU adhesives, combined with surface electrophoresis and hot air drying technology, prepare PVC to produce PVC /Ncc@PU/ECG@PVDC composite hard film.

Benefits of technology

It significantly improves the aging performance of complex hardcores, blocking water vapor and oxygen, and improved its mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117487224B_ABST
    Figure CN117487224B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a plastic composite hard sheet, wherein the preparation method comprises the following steps: 1) dissolving ECG powder in a PVDC emulsion at a mass ratio of 1:500-200 to obtain an ECG@PVDC composite emulsion; 2) adding nanocellulose NCC to an adhesive waterborne polyurethane at a mass ratio of 1:100-10000 to obtain an NCC@PU waterborne adhesive; 3) performing a surface corona treatment on a PVC hard sheet, coating the NCC@PU adhesive on the corona-treated PVC hard sheet, and then coating the ECG@PVDC emulsion on the NCC@PU adhesive layer after hot air drying, and curing the coated sheet at a temperature of 20-40°C for 48 hours to obtain a plastic composite hard sheet. The plastic composite hard sheet prepared by the preparation method of the invention has the advantages of strong resistance to ultraviolet radiation, high water vapor and oxygen barrier performance, and stronger mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical packaging materials, and specifically provides a preparation method and application of a plastic composite hard sheet. Background Art

[0002] Polyvinylidene chloride (PVDC) emulsion is a white water-soluble latex-like opaque liquid. It is made by emulsion polymerization of vinylidene chloride and acrylate. It is mainly used for coating a series of plastic products. With PVC, PS, PET and other substrates, PVDC emulsion is coated on the surface of the substrate to prepare a composite plastic hard sheet, which can be used for packaging of medicines, food, cosmetics and other products. Since the PVDC molecular chain contains a large number of polar chlorine atoms, oxygen molecules and water molecules are difficult to move in the PVDC molecules, and the PVDC emulsion has excellent ability to block water vapor and oxygen after being coated on PVC, PC, PET and other materials to form a film, it can effectively prevent product deliquescence, oxidation deterioration and odor problems, thereby extending the shelf life of the product. Commercial composite hard sheets for pharmaceutical packaging also need to be coated with a layer of water-based polyurethane (PU) adhesive between the PVC layer and the PVDC layer to ensure that the PVDC layer is tightly bonded to the PVC layer and does not fall off. Currently, the commercially available PVC / PU / PVDC composite hard sheets have problems such as poor aging resistance and yellowing of the PVDC layer due to the influence of heat and ultraviolet radiation.

[0003] Epicatechin gallate (ECG) has the molecular formula C 22 H 18 O 10 Molecular structure Figure 1 As shown. ECG is the most effective active ingredient in tea polyphenols, with antibacterial, antiviral and antioxidant properties. Nanocellulose (NCC) is a representative of cellulose-based nanomaterials. It not only retains the properties of natural cellulose, but also gives nanoparticles high strength, high crystallinity, high specific surface area, high tensile strength and other properties, which can significantly improve the optical, electrical, magnetic, strength and other properties of the material. The reinforcing ability of nanocellulose after combining with different matrices is due to the strong interaction between the fibers, thereby improving the mechanical properties of its composite material. When the concentration of nanocellulose reaches a certain level, the nanofiber network can be considered as the result of a permeation mechanism, and the hydrogen bonds between them increase, thereby improving the mechanical properties of the composite material. Consider adding nanocellulose (NCC) to the water-based polyurethane adhesive used in coating PVC / PVDC composite hard sheets to see if it can improve the anti-aging performance, anti-ultraviolet performance and water vapor barrier capacity of PVC / PVDC composite hard sheets and improve their brittleness problem. Summary of the invention

[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide a preparation method and application of a new type of medicinal composite hard sheet with comprehensive properties such as anti-ultraviolet aging performance and water vapor barrier performance that are better than the existing PVC / PU / PVDC composite hard sheet.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing a plastic composite hard sheet comprises the following steps:

[0007] 1) dissolving ECG powder in PVDC emulsion at a mass ratio of 1:500-200 to obtain ECG@PVDC composite emulsion;

[0008] 2) adding nanocellulose NCC to adhesive waterborne polyurethane at a mass ratio of 1:100-10000, mixing evenly, and obtaining NCC@PU waterborne adhesive;

[0009] 3) The surface of the PVC hard sheet is subjected to corona treatment, and a layer of NCC@PU adhesive is coated on the corona-treated PVC hard sheet. After coating, ECG@PVDC emulsion is continuously coated on the NCC@PU adhesive layer after hot air drying. The coated sheet is aged at a temperature of 20-40°C for 48 hours to obtain a PVC / NCC@PU / ECG@PVDC plastic composite hard sheet.

[0010] Preferably, in step 1), the mass ratio of ECG powder to PVDC emulsion is 1:1000.

[0011] Preferably, the solid content of the aqueous polyurethane liquid in step 2) is 35%, the viscosity is 100 mPa·s, and the density is 1.02 g / cm 3 , this product can be purchased from Covestro Resins Manufacturing (Foshan) Co., Ltd.

[0012] Preferably, in step 2), the solid content of nanocellulose NCC is 2.5-3.5%, the length is 1-10 microns, the diameter is 20-50 nanometers, and the density is 1.007 g / cm 3 .

[0013] Preferably, in step 2), the mass ratio of the nanocellulose NCC to the aqueous polyurethane is 1:300.

[0014] Preferably, the thickness of the PVC hard sheet in step 3) is 200 μm-400 μm, preferably 250 μm, and the density is 1.35-1.45 g / cm 3 , preferably 1.40g / cm 3 The coating amount of NCC@PU adhesive is 1.5g / m 2 .

[0015] Preferably, the temperature of the hot air drying treatment in step 3) is 60-90° C., preferably 80° C., and the drying time is 10-30 s, preferably 20 s.

[0016] Preferably, the coating amount of ECG@PVDC emulsion in step 3) is 20-90 g / m 2 , preferably 40g / m 2 The coating is completed in three times, namely primer, additional coating and top coating. After primer, additional coating and top coating are completed, hot air drying is required at 60-90℃ for 20-80s.

[0017] The coating amount during the primer coating is determined by the coating speed. The hot air at 60-90°C (preferably 80°C) is used for drying for 20-80s (preferably 30s). After drying, a layer of ECG@PVDC emulsion is applied. The coating amount during the additional coating is determined by the coating speed and the scraper gap. The hot air at 60-90°C (preferably 80°C) is used for drying for 20-80s (preferably 30s). After drying, the coating amount is checked. If the coating amount is not enough, a top coating is performed again. According to the coating amount after the additional coating, a suitable coating roller is selected for another top coating. After drying, the coating amount is tested. If the coating amount is too large, it is a defective product. If the coating amount is too small, repeat the top coating. This coating method is more in line with actual production. The ECG@PVDC composite emulsion is applied three times for more uniform coating. At the same time, the coating amount is more accurately controlled, making the experiment more rigorous and making the subsequent water vapor transmission rate and oxygen transmission rate test results more convincing.

[0018] Application of the plastic composite hard sheet prepared by any of the preparation methods described in 1-8 above in pharmaceutical packaging materials.

[0019] In the present invention, the PVDC emulsion can be prepared by a known method, specifically, for example, it can be prepared according to the method of Example 1 of Chinese Patent Publication No. CN104114585A; the nanocellulose (NCC) can also be prepared by a known method, specifically, for example, a modified nanocellulose can be prepared according to the method of Example 1 of Chinese Patent Publication No. CN115028898A. The nanocellulose (NCC) prepared by this method has good dispersibility, uniform size, and low preparation cost.

[0020] Compared with the prior art, the plastic composite hard sheet prepared by the preparation method of the present invention has the advantages of strong resistance to ultraviolet radiation, high water vapor and oxygen barrier performance, and stronger mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the molecular structure diagram of epicatechin gallate (ECG);

[0022] Figure 2It is a schematic diagram of the cross-sectional structure of a PVC / PU / PVDC composite hard sheet;

[0023] Figure 3 Schematic diagram of the cross-sectional structure of the PVC / NCC@PU / ECG@PVDC composite hard sheet prepared in Example 1;

[0024] Figure 4 is a comparison chart of the UV-visible transmission spectra of the PVC / NCC@PU / ECG@PVDC composite hard sheet prepared in Example 1 and the PVC / PU / PVDC composite hard sheet;

[0025] Figure 5 It is a comparison chart of the water vapor transmission rate test results of the PVC / NCC@PU / ECG@PVDC composite hard sheet prepared in Example 1 and the PVC / PU / PVDC composite hard sheet;

[0026] Figure 6 It is a comparison chart of the oxygen permeability test results of the PVC / NCC@PU / ECG@PVDC composite hard sheet prepared in Example 1 and the PVC / PU / PVDC composite hard sheet. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with specific embodiments to facilitate a better understanding of the present technical solution.

[0028] Example 1

[0029] Preparation of ECG@PVDC composite emulsion: PVDC emulsion prepared according to the method of Example 1 of Chinese Patent Publication No. CN104114585A;

[0030] 1 g of epicatechin gallate (ECG) powder was dissolved in 1000 g of PVDC emulsion and mixed evenly to obtain ECG@PVDC composite emulsion.

[0031] Preparation of NCC@PU composite adhesive: A modified nanocellulose was prepared according to the method of Example 1 of Chinese Patent Publication No. CN115028898A;

[0032] 2 g of nanocellulose was added to 600 g of aqueous polyurethane (PU) liquid with a solid content of 35% to obtain NCC@PU water-based adhesive.

[0033] Preparation of PVC / NCC@PU / ECG@PVDC composite hard sheet: 3 (Preferably 1.40 g / cm 3 ), a PVC hard sheet with a thickness of 200 μm-400 μm (preferably 250 μm) is subjected to surface corona treatment, and then 1.5 g / m 2A layer of NCC@PU adhesive is applied on the corona treated PVC hard sheet. After coating, it is dried with hot air at 60-90℃ (preferably 80℃) for 10-30s (preferably 20s). Then, a layer of NCC@PU adhesive is applied at a coating weight of 20-90g / m 2 (Preferably 40g / m 2 ) coating amount, and the emulsion coating is completed in three times, namely, primer coating, additional coating and top coating. After the adhesive layer is dried, a layer of ECG@PVDC emulsion is first applied as a primer. The coating amount during primer coating is determined by the coating speed. Hot air drying at 60-90°C (preferably 80°C) is used for 20-80s (preferably 30s). After drying, another layer of ECG@PVDC emulsion is applied. The coating amount during additional coating is determined by the coating speed and the scraper gap. Hot air drying at 60-90°C (preferably 80°C) is used for 20-80s (preferably 30s). After drying, the coating amount is checked. If the coating amount is not enough, top coating is performed again. According to the coating amount after additional coating, a suitable coating roller is selected for another top coating. After drying, the coating amount is tested. If the coating amount is too large, it is a defective product. If the coating amount is too small, repeat the top coating. The coated sheet that has passed the coating amount test is placed at 20-40°C for 48 hours to finally obtain a PVC / NCC@PU / ECG@PVDC composite hard sheet, the cross-sectional structure diagram of which is shown in the figure. Figure 3 shown.

[0034] Comparative Example

[0035] PVDC emulsion was prepared according to the method of Example 1 of Chinese Patent Publication No. CN104114585A. 3 , the surface of PVC hard sheet with a thickness of 250μm was corona treated, and then 2 A layer of PU adhesive is applied on the corona treated PVC hard sheet. After coating, it is dried with hot air at 80°C for 20 seconds. Then, a layer of PU adhesive is applied on the adhesive (PU) layer at a coating weight of 20-90g / m 2 (Preferably 40g / m 2) coating amount, and the emulsion coating is completed in three times, namely, primer coating, additional coating and top coating. After the adhesive layer is dried, a layer of PVDC emulsion is first applied as a primer. The coating amount during primer coating is determined by the coating speed. Hot air drying at 60-90°C (preferably 80°C) is used for 20-80s (preferably 30s). After drying, another layer of PVDC emulsion is applied. The coating amount during additional coating is determined by the coating speed and the scraper gap. Hot air drying at 60-90°C (preferably 80°C) is used for 20-80s (preferably 30s). After drying, the coating amount is checked. If the coating amount is not enough, top coating is performed again. According to the coating amount after additional coating, a suitable coating roller and coating speed are selected for another top coating. After drying, the coating amount is tested. If the coating amount is too large, it is a defective product. If the coating amount is too small, repeat the top coating. The coated sheet that has passed the coating amount test is placed at 20-40°C for 48 hours to finally obtain a PVC / PU / PVDC composite hard sheet, the cross-sectional structure diagram of which is shown in the figure. Figure 2 shown.

[0036] Test Method

[0037] The sheets made according to Example 1 and the control example were tested for packaging material properties such as UV-visible light transmission spectrum, water vapor transmission rate, and oxygen transmission rate. The UV-visible light transmission spectrum was tested using an ultraviolet spectrometer (UV-2550 model from SHIMADZU), the water vapor transmission rate was tested using a water vapor transmission rate meter (MPVDC / PVCULE model from MOCON, USA), and the oxygen transmission rate was tested using an oxygen transmission rate meter (OX-Tran series from MOCON, USA).

[0038] The comparison of the UV-visible transmission spectra of the PVC / NCC@PU / ECG@PVDC composite sheet prepared in Example 1 and the PVC / PU / PVDC composite sheet is shown in FIG. Figure 4 As shown, according to Figure 4 It can be seen from the UV-visible light transmission spectrum that the PVC / NCC@PU / ECG@PVDC composite hard sheet made according to Example 1 can block more UV light than the PVC / PU / PVDC composite hard sheet, thereby improving the anti-aging performance of the composite hard sheet.

[0039] The comparison of the water vapor transmission rate test results of the PVC / NCC@PU / ECG@PVDC composite sheet prepared in Example 1 and the PVC / PU / PVDC composite sheet is shown in the figure below: Figure 5 As shown, from Figure 5 It can be seen that the plastic composite hard sheet prepared by the present invention has a strong water vapor barrier capability.

[0040] The comparison of oxygen transmission rate test results of PVC / NCC@PU / ECG@PVDC composite sheet prepared in Example 1 and PVC / PU / PVDC composite sheet is shown in the figure below: Figure 6 As shown, according to Figure 6 The analysis of the oxygen permeability spectrum shows that PVC / PU / PVDC sheets have good oxygen barrier properties, but the oxygen barrier properties of PVC / NCC@PU / ECG@PVDC composite sheets are further improved compared to PVC / PVDC.

Claims

1. A method for preparing a plastic composite hard sheet, characterized in that: The method comprises the following steps: 1) dissolving ECG powder in PVDC emulsion at a mass ratio of 1:500-200 to obtain ECG@PVDC composite emulsion; 2) Adding nanocellulose NCC to adhesive waterborne polyurethane at a mass ratio of 1:100-10000, mixing evenly, and obtaining NCC@PU waterborne adhesive; 3) The surface of the PVC hard sheet is subjected to corona treatment, and a layer of NCC@PU adhesive is coated on the corona-treated PVC hard sheet. After coating, ECG@PVDC emulsion is continuously coated on the NCC@PU adhesive layer after hot air drying. The coated sheet is cured at a temperature of 20-40°C for 48 hours to obtain a PVC / NCC@PU / ECG@PVDC plastic composite hard sheet.

2. The method for preparing a plastic composite hard sheet according to claim 1, characterized in that In step 1), the mass ratio of ECG powder to PVDC emulsion is 1:1000.

3. The method for preparing a plastic composite hard sheet according to claim 1, characterized in that Step 2) The solid content of the aqueous polyurethane liquid is 35%, the viscosity is 100mPa·s, and the density is 1.02g / cm 3 .

4. The method for preparing a plastic composite hard sheet according to claim 1, characterized in that Step 2) The solid content of nanocellulose NCC is 2.5-3.5%, the length is 1-10 microns, the diameter is 20-50 nanometers, and the density is 1.007 g / cm 3 .

5. The method for preparing a plastic composite hard sheet according to claim 1, characterized in that The mass ratio of nanocellulose NCC to waterborne polyurethane in step 2) is 1:

300.

6. The method for preparing a plastic composite hard sheet according to claim 1, characterized in that In step 3), the thickness of the PVC hard sheet is 200μm-400μm and the density is 1.35-1.45g / cm 3 The coating amount of NCC@PU adhesive is 1.5 g / m 2 .

7. The method for preparing a plastic composite hard sheet according to claim 1, characterized in that In step 3), the temperature of the hot air drying treatment is 60-90°C and the time is 10-30s.

8. The method for preparing a plastic composite hard sheet according to claim 1, characterized in that In step 3), the coating amount of ECG@PVDC emulsion is 20-90 g / m 2 The coating is completed in three times, namely primer, additional coating and top coating. After primer, additional coating and top coating are completed, hot air drying is required at 60-90℃ for 20-80s.

9. Use of the plastic composite hard sheet obtained by the preparation method according to any one of claims 1 to 8 in pharmaceutical packaging materials.

Citation Information

Patent Citations

  • Vinylidene chloride copolymer latex and film for blister pack

    CN104114585A

  • Preparation method and application of plastic composite hard sheet modified by bamboo leaf extract

    CN116444840A

  • Preparation method and application of nano-cellulose modified plastic composite hard sheet

    CN116655978A